1999
DOI: 10.1136/fn.80.1.f49
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of congenital heart disease in infancy: implications for routine examination

Abstract: Aim-To investigate the performance of routine neonatal and 6 week examinations for detecting congenital heart disease. Methods-A retrospective review of findings on clinical examination was conducted of a cohort of live born infants with congenital heart disease in one health region in 1987-94 Results-Of 1590 babies with congenital heart disease, 523 (33%) presented before neonatal examination because of symptoms or non-cardiac abnormalities. 1061 underwent routine neonatal examination which was abnormal in 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
220
2
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(246 citation statements)
references
References 13 publications
10
220
2
14
Order By: Relevance
“…Two new Class I recommendations and one Class III recommendation have been added. [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194] One recommendation has moved from Class IIb to Class IIa. Class I recommendations have been renumbered for clarity.…”
Section: Recommendations For Neonatal Echocardiographymentioning
confidence: 99%
“…Two new Class I recommendations and one Class III recommendation have been added. [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194] One recommendation has moved from Class IIb to Class IIa. Class I recommendations have been renumbered for clarity.…”
Section: Recommendations For Neonatal Echocardiographymentioning
confidence: 99%
“…Other presentations can range from cyanosis, clubbing of fingers, fatigue to full blown congestive cardiac failure (7,9). CHD has not been studied thoroughly in India, as in western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advanced diagnostic facilities and improved medical care, CHD is considered one of the leading causes of infant mortality (7). According to a status report on CHD in India, 10% of the present infant mortality may be accounted by CHD (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However several studies have reported that the examination does not perform well as a screening tool. [15][16][17][18][19][20] An appropriate test of quality would be how far practitioners adhere to agreed best practice in administering the examination and this could be assessed with the aid of video recordings. In psychological research, video recordings are often used for assessments with subsequent structured evaluation of objectivity and quality of administration by examiners.…”
mentioning
confidence: 99%